Clinical exome sequencing by general pediatricians: high clinical utility and no evidence of inappropriate testing - Baz, Danya Salah; Baz, Dareen; Alrwuili, Fawzah; Aldowaish, Abdullah; Shamseldin, Hanan E.; Elhomoudi, Ayman; Alkuraya, Fowzan S. (Frontiers in Pediatrics, 2024)
Background Genetic disorders account for a large percentage of admissions and outpatient visits to children’s hospitals around the world. Clinical Exome Sequencing (CES) is a valuable diagnostic tool for these disorders; however, it is not routinely requested by general pediatricians. This may represent a missed opportunity to increase patient access to this powerful diagnostic tool. In our institution, general pediatricians can directly order CES. This study aims to evaluate the appropriateness of CES and its clinical utility when ordered by general pediatricians. Methods We retrospectively reviewed all CES tests ordered by general pediatricians in our institution between 2019 and 2023 and recorded their indications and results. . General pediatricians were interviewed to evaluate how CES impacted the domains of clinical utility by assessing changes in management, communication, subsequent testing, and counseling. In addition, feedback was obtained, and barriers faced by general pediatricians to order CES were assessed. Results The study cohort (n=30) included children from the inpatient (60%) and outpatient (40%) departments. A positive finding (a pathogenic or likely pathogenic variant that explains the phenotype) was observed in 11 of 30 cases (37%), while 3 (10%) and 16 (53%) received ambiguous (variant of uncertain significance, VUS) and negative results, respectively. The indication was deemed appropriate in all 30 cases (100%). Clinical utility was reported in all 11 positive cases (100%). Reproductive counseling is a notable utility in this highly consanguineous population as all variants identified, in the eleven positive cases, were autosomal recessive. Conclusion We show that CES ordered by general pediatricians is appropriately indicated and provides a diagnostic yield comparable to that requested by specialists. Additionally, we note the high clinical utility of positive results as judged by the ordering pediatricians. The study’s findings can empower general pediatricians to advocate for expanded CES adoption to improve patient access and shorten their diagnostic odyssey.